2014
DOI: 10.1007/s00432-014-1880-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 1B1 (CYP1B1) polymorphisms are associated with clinical outcome of docetaxel in non-small cell lung cancer (NSCLC) patients

Abstract: CYP1B1 4326C>G polymorphism emerged as possible prognostic/predictive marker of activity and efficacy of docetaxel in NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…These investigators, however, observed no association between CYP1B1*4 polymorphisms and survival in patients with NSCLC. In line with Vasile et al 19 , Ada et al 7 previously showed that the CYP1B1*4 polymorphism was not associated with survival in patients with NSCLC, although a notable trend towards worsening of survival in CYP1B1*4 mutant allele carriers was determined (Table 4).…”
Section: The Associations Between Cyp Polymorphisms and Response To Csupporting
confidence: 57%
See 3 more Smart Citations
“…These investigators, however, observed no association between CYP1B1*4 polymorphisms and survival in patients with NSCLC. In line with Vasile et al 19 , Ada et al 7 previously showed that the CYP1B1*4 polymorphism was not associated with survival in patients with NSCLC, although a notable trend towards worsening of survival in CYP1B1*4 mutant allele carriers was determined (Table 4).…”
Section: The Associations Between Cyp Polymorphisms and Response To Csupporting
confidence: 57%
“…7 There are only two studies in regard to the influences of CYP1B1 polymorphisms on survival in lung cancer (Table 4). Recently, Vasile et al 19 demonstrated that CYP1B1*3 mutant allele carriers had shorter survival compared with wild-type allele carriers. These investigators, however, observed no association between CYP1B1*4 polymorphisms and survival in patients with NSCLC.…”
Section: The Associations Between Cyp Polymorphisms and Response To Cmentioning
confidence: 99%
See 2 more Smart Citations
“…The 5-year survival rate of NSCLC is estimated to be 15% and the median survival time is less than 10 months (NCCN, 2011). An increasing number of genomic studies have reported potential therapeutic targets in lung cancer, such as XRCC1, XPF, XPG, CYP1B1, and OPN genes (Hao et al, 2014;Shi et al, 2015;Vasile et al, 2015;Zou and Zhao, 2015).…”
Section: Introductionmentioning
confidence: 99%